Sm‐p80‐based schistosomiasis vaccine: double‐blind preclinical trial in baboons demonstrates comprehensive prophylactic and parasite transmission‐blocking efficacy. Issue 1 (10th August 2018) - Zhang, Weidong; Molehin, Adebayo J.; Rojo, Juan U.; Sudduth, Justin; Ganapathy, Pramodh K.; Kim, Eunjee; Siddiqui, Arif J.; Freeborn, Jasmin; Sennoune, Souad R.; May, Jordan; Lazarus, Samra; Nguyen, Catherine; et al.
Abstract: Schistosomiasis is of public health importance to an estimated one billion people in 79 countries. A vaccine is urgently needed. Here, we report the results of four independent, double‐blind studies of an Sm‐p80‐based vaccine in baboons. The vaccine exhibited potent prophylactic efficacy against transmission of Schistosoma mansoni infection and was associated with significantly less egg‐induced pathology, compared with unvaccinated control animals. Specifically, the vaccine resulted in a 93.45% reduction of pathology‐producing female worms and significantly resolved the major clinical manifestations of hepatic/intestinal schistosomiasis by reducing the tissue egg‐load by 89.95%. A 35‐fold decrease in fecal egg excretion in vaccinated animals, combined with an 81.51% reduction in hatching of eggs into the snail‐infective stage (miracidia), demonstrates the parasite transmission‐blocking potential of the vaccine. Substantially higher Sm‐p80 expression in female worms and Sm‐p80‐specific antibodies in vaccinated baboons appear to play an important role in vaccine‐mediated protection. Preliminary analyses of RNA sequencing revealed distinct molecular signatures of vaccine‐induced effects in baboon immune effector cells. This study provides comprehensive evidence for the effectiveness of an Sm‐p80‐based vaccine for schistosomiasis. Abstract : Schistosomiasis is of public health importance to an estimated one billion people in 79 countries. A vaccine is urgently needed. Here, we report the results of four independent, double‐blind studies of an Sm‐p80‐based vaccine in baboons. The vaccine exhibited potent prophylactic efficacy against transmission of Schistosoma mansoni infection and was associated with significantly less egg‐induced pathology, compared with unvaccinated control animals.